Prevalence of overweight and obesity among the urban adolescent English Medium School girls of Kolkata, India (Italian Journal of Public Health, 2012)
Background: the prevalence of child obesity is increasing rapidly worldwide. In developing countries such as India, especially in urban populations, childhood obesity is emerging as a major health problem. In view of these contexts, the present study was undertaken to estimate the prevalence of overweight and obesity in an urban population of girl adolescent students attending the English Medium School in Kolkata, India.Methods: a total of 571 girl students, aged 12-18 years, were evaluated. Cole et al. (2000) recommended cut-off points were utilized to assess overweight and obesity.Results: the overall prevalence rates of overweight and obesity were 28.5% and 4.2% respectively. The rate of overweight was the highest when compared with that of different parts of India, including Kolkata, and also when compared to rates from the USA and Great Britain.Conclusions: in the context of the present study, it can be presumed that, the higher prevalence of overweight in these school children may be due to their eating habits, as well as to their lack of awareness on proper eating habits. In addition, low involvement in physical activities may also have influenced the rate of overweight and obesity. Thus, it can be concluded that the study definitely highlighted the existence of an obesity threat, which is likely to persist among Bengalee school children of wealthier families.
Keywords: Overweight; Obesity; Adolescent school girls; Kolkata